Effect Of Chitosan and Whey Powder on The Physiological Status of Broiler Chicks Fed - Rahmonov F.X.; Eshimov D.; Islamov X.I (Zien Journals, 2023)
Today, in our republic, as in all countries, the development of poultry farming is considered an important factor in ensuring food security, and the industry has an incomparable role in providing the population with dietary poultry meat and egg products rich in proteins and vitamins. The dry and warm climate of Uzbekistan is favorable for keeping and raising poultry.
Keywords: Chitosan; chitin; broiler